Identification of wood destruction during drying - J. Kowalski, Stefan; Smoczkiewicz, Anna (Maderas. Ciencia y Tecnología, 2014)
The subject of this paper concerns destruction of timber during drying. The main goal is to propose a method of avoiding destruction through a suitable programming of drying processes, controlled with the help of the acoustic emission (AE) method. Three different programs of convective drying of pinewood (Pinus sp.) samples are presented. The high and slow rate drying programs were applied to show an evident dependence between the intensity of AE signals (their number and energy) and the degree of destruction of pinewood during drying. The third drying program was controlled, i.e. the drying was accelerated, when the acoustic emission was low, or slowed down, when the acoustic emission started to grow rapidly. In this way , the drying process was optimized for the purpose of shortening of the drying time and avoiding a destruction of the material.